COVID‐19 outbreak in Lombardy: Impact on reducing solid cancer diagnoses in 2020. Issue 9 (8th July 2022) - Trama, Annalisa; Bernasconi, Alice; Botta, Laura; Di Cosimo, Serena; Miceli, Rosalba; Claps, Melanie; Badenchini, Fabio; Lillini, Roberto; Rubino, Massimiliano; Lasalvia, Paolo
Abstract: Our aim was to analyse, on a population level, the year‐long decline in cancer diagnoses in the region of Lombardy (Italy), and to characterise the tumours with the greatest reduction in diagnosis by patient age, sex and tumour stage at diagnosis. We used the health care utilisation databases of the Lombardy region to identify cancer patients' characteristics (eg, sex, age) and cancer‐related information (eg, cancer site, stage at diagnosis). The frequency of new cancer diagnoses in 2019 and 2020 were compared in terms of percentage differences in undiagnosed cases. We observed two peaks in the decline in cancer diagnoses: March to May 2020 (−37%) and October to December 2020 (−19%). The decline persisted over the course of 2020 and was higher in males and patients aged 74+. Diagnoses of all four common cancers analysed (female breast, lung, colorectal and prostate) remained below pre‐pandemic levels. For breast and colorectal cancers, the decline in diagnoses was high in the age groups targeted by population‐based screening programmes. We observed a reduction in localised stage cancer diagnoses for all four cancers. Our data confirm that timely monitoring of cancer diagnoses and interventions to prevent disruption of routine diagnostic services are needed to mitigate the impact of emergencies on cancer patients. Abstract : What's new? The impact of COVID‐19 restrictions on cancer diagnosis and treatment has become a widespread source of concern. This population‐based study reports a persisting decline in new cancer diagnoses during 2020 compared to pre‐pandemic levels and a reduction in localised‐stage cancer diagnoses for female breast, lung, prostate and colorectal cancer. Moreover, our study reveals inequalities across cancer patient groups, with males and patients over 74 being more negatively impacted by the COVID‐19 pandemic. Timely monitoring of cancer diagnoses and interventions to prevent disruption of routine diagnostic services are needed to mitigate the impact of public health emergencies on cancer patients.